Renegotiation without holdup: anticipating spending and infrastructure concessions - Eduardo M. R. A. Engel; Ronald D. Fischer; Alexander Galetovic (Yale University, Economic Growth Center, 2006)
Infrastructure concessions are frequently renegotiated after investments are sunk, resulting in better contractual terms for the franchise holders. This paper offers a political economy explanation for renegotiations that occur with no apparent holdup. We argue that they are used by political incumbents to anticipate infrastructure spending and thereby increase the probability of winning an upcoming election. Contract renegotiations allow administrations to replicate the effects of issuing debt. Yet debt issues are incorporated in the budget, must be approved by Congress and are therefore subject to the opposition's review. By contrast, under current accounting standards the obligations created by renegotiations circumvent the budgetary process in most countries. Hence, renegotiations allow incumbents to spend more without being subject to Congressional oversight.
Keywords: H21; L51; L91; 330; build-operate-and-transfer (BOT); concessions; renegotiation; public-private partnerships